2017
DOI: 10.1590/s1677-5538.ibju.2016.0571
|View full text |Cite
|
Sign up to set email alerts
|

Nephrometry scores and perioperative outcomes following robotic partial nephrectomy

Abstract: Objectives:Based on imaging features, nephrometry scoring systems have been conceived to create a standardized and reproducible way to characterize renal tumor anatomy. However, less is known about which of these individual measures are important with regard to clinically relevant perioperative outcomes such as ischemia time (IT), estimated blood loss (EBL), length of hospital stay (LOS), and change in estimated glomerular filtration rate (eGFR) after robotic partial nephrectomy (PN). We aimed to assess the ut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…They concluded these features could be used individually as a simplified way to report tumor features for research and patient counseling purposes. 26 Ficarra et al proposed recently the simplified PADUA REnal score. This new SPARE score is comprised of only four variables instead of the original six and its accuracy to predict overall complications is similar to that of the original PADUA score.…”
Section: Dovepressmentioning
confidence: 99%
“…They concluded these features could be used individually as a simplified way to report tumor features for research and patient counseling purposes. 26 Ficarra et al proposed recently the simplified PADUA REnal score. This new SPARE score is comprised of only four variables instead of the original six and its accuracy to predict overall complications is similar to that of the original PADUA score.…”
Section: Dovepressmentioning
confidence: 99%
“…Investigators have published contradictory results on this issue. Corradi et al 46 reporting data from 283 patients who underwent RPN, found a significant correlation between the three scores and EBL and LOS. In the study by Kwon et al 23 , all the three scores were useful for predicting EBL, and at least one could correlate with OT and LOS.…”
Section: Discussionmentioning
confidence: 99%
“…In addition the patient-side assistant should be appropriately skilled in handling instruments safely and deploying ligature clips. All cases should be subjected to nephrometry scoring (PADUA and RENAL) and a thorough imaging review preoperatively to predict operative complexities and postoperative complications [13][14][15][16]. We incorporate the PADUA score due to its standardised use across the national nephrectomy register, collected by the British Association of Urological Surgeons.…”
Section: Introductionmentioning
confidence: 99%